State Senior Games Participant Motivation - Shawver, sandra Kay (Journal of Amateur Sport, 2020)
Sport provides many benefits to all who participate, from being socially mobile, to challenging one’s physical abilities. It offers opportunities for individual improvement in quality of life, self-confidence, and socialization. The National Senior Games Association (NSGA) exists to assist seniors (50+) in achieving a greater quality of life through activity and positive lifestyle opportunities. As interest in the area of sport motivation for senior adults continues to expand, there is still little information specific to the National Senior Games participants. This research contributes to the sport management literature by providing the basis of generalized information about NSGA participant demographic backgrounds and how they are motivated to participate in the individual state games held each year. Gaining pertinent information concerning the motivations of senior games participants, this study sought to identify specific motivation levels based on gender and the state of participation that may assist local and state organizations in the development and growth of similar events. Using the Sport Motivation Scale-6, demographic, and psychographic information results indicated that participants in different states are motivated differently and that participation is more personally important to women. Both genders were involved for the opportunity to challenge their abilities, improve or maintain their current health, and have a social connection to others.   Keywords: Senior Sports, National Senior Games, Older Adults, Motivation